The telltale targets: an analysis of access errors in the speech of intermediate students of spanish - Lafford, Bárbara A.; Collentine, Joseph G. (Lenguas Modernas, 2017)
This cross-sectional study of the oral interlanguage of forty students at the end of their fourth semester of universitv level Spanish, measures the accuracy with which correct forms were produced vis-a-vis the following grammatical categories: aspect, number, person, mood, tense and gender. The results of the study show that gender was the most problenratic of the atirrementioned categories. In adittion, within each category a positive correlation was found between frecuency of the required use of the unmarked form and the accuracy with which it was realized. Finally plausible explanations for these phenomena are offered.